Vers la construction d’un capital environnemental par la lutte contre un projet d’aménagement ? Le barrage de Loyettes (Rhône-Alpes) - Silvia Flaminio; Yves-François Le Lay (Développement Durable et Territoires)
The Loyettes dam, planned on the Upper Rhône River, is one of the first dams to have been cancelled in France; the project was blocked during the legal public enquiry in 1982 before being completely abandoned in 1990. The study of the Loyettes controversy is based on interviews carried out 30 years later (n =17) and on archive documents (from local, regional, national public archives and from private archives). The paper aims to show the growing complexity of a specific value system. Because of the growing complexity of the value system during the controversy, and of the current and poor enhancement of the site, the site can only be considered as an unfulfilled « environmental capital ».